Hubungan Timbal Balik antara Kinerja dan Komitmen Organisasi: Studi tentang Sektor Industri Restoran Cina - Leonardo Indra Vitaharsa; Aris Budiono (Yayasan Literasi Sains Indonesia, 2026)
This study explores the reciprocal relationship between job performance and organisational commitment in the context of the Chinese food restaurant industry in Jakarta. Drawing on social exchange theory and triadic reciprocal causality, the study investigates how these two variables reinforce each other in a dynamic and socially intensive work environment. Using a quantitative approach, data were collected from employees at several restaurant locations through a structured questionnaire. The analysis revealed a statistically significant bidirectional effect, indicating that job performance contributes to strengthening organisational commitment, while organisational commitment also enhances individual job performance. The regression model used in this study was validated through classical assumption tests and demonstrated strong explanatory power. These findings underscore the importance of integrating performance and commitment strategies in human resource management to foster employee engagement, increase productivity, and support long-term organisational sustainability. Practical implications include the need for equitable recognition systems, ongoing training, and the development of a participatory and supportive work environment.